Advances in the roles and mechanisms of lignans against Alzheimer’s disease - Han, Na; Wen, Yuanyuan; Liu, Zhihui; Zhai, Jianxiu; Li, Sikai; Yin, Jun (Frontiers in Pharmacology, 2022)
Background: Alzheimer’s disease (AD) is a serious neurodegenerative disease associated with the memory and cognitive impairment. The occurrence of AD is due to the accumulation of amyloid β-protein (Aβ) plaques and neurofibrillary tangles (NFTs) in the brain tissue as well as the hyperphosphorylation of Tau protein in neurons, doing harm to the human health and even leading people to death. The development of neuroprotective drugs with small side effects and good efficacy is focused by scientists all over the world. Natural drugs extracted from herbs or plants have become the preferred resources for new candidate drugs. Lignans were reported to effectively protect nerve cells and alleviate memory impairment, suggesting that they might be a prosperous class of compounds in treating AD. Objective: To explore the roles and mechanisms of lignans in the treatment of neurological diseases, providing proofs for the development of lignans as novel anti-AD drugs. Methods: Relevant literature was extracted and retrieved from the databases including China National Knowledge Infrastructure (CNKI), Elsevier, Science Direct, PubMed, SpringerLink, and Web of Science, taking lignan, anti-inflammatory, antioxidant, apoptosis, nerve regeneration, nerve protection as keywords. The functions and mechanisms of lignans against AD were summerized. Results: Lignans were found to have the effects of regulating vascular disorders, anti-infection, anti-inflammation, anti-oxidation, anti-apoptosis, antagonizing NMDA receptor, suppressing AChE activity, improving gut microbiota, so as to strengthening nerve protection. Among them, dibenzocyclooctene lignans were most widely reported and might be the most prosperous category in the develpment of anti-AD drugs. Conclusion: Lignans displayed versatile roles and mechanisms in preventing the progression of AD in in vitro and in vivo models, supplying potential candidates for the treatment of nerrodegenerative diseases.